The Effect of Mirror Therapy on Muscle Strength in Non Hemorrhagic Stroke Patients in Sembiring General Hospital - Zuliawati .; Meta Rosaulina; Reisy Tane (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Stroke sufferers generally experience motor disorders, where the most typical symptom is damage or death of brain tissue which can cause symptoms of disability in the form of hemiparesis of limbs or weakness of extremity muscles which can cause limitations in mobilization. The intervention given can be in the form of range of motion exercises using mirror therapy (mirror therapy) to increase muscle strength by including the perception of visual illusions to increase the movement of limbs experiencing hemiparesis. The purpose of this study was to determine the effect of mirror therapy on muscle strength in non hemorrhagic stroke patients. This research method uses a quasi experiment with a one group pre test post test research design. The population is all non hemorrhagic stroke patients at Sembiring General Hospital with a sampling technique using purposive sampling obtained as many as 11 respondents. The research instrument used observation sheets and SOPs. Analysis test using Wilcoxon Signed Ranks Test obtained p value = 0.003 (p <0.05). Conclusion: there is an effect of mirror therapy on muscle strength in non hemorrhagic stroke patients so that it can be considered as one of the treatment measures to improve motor function and increase muscle strength in non hemorrhagic stroke patients.